Taxonomic Revision of Fern-Allies Lycopodiaceae Mirbel in Malaysia - Kongoi, Clasius @ Claysius (2004)
The family Lycopodiaceae in Malaysia consists of three genera, namely, Huperzia, Lycopodium and Lycopodiella and comprises 32 species, including 11 varieties. Four species are reported as new records for Malaysia (Huperzia beccarii, H. goliathensis, H. prolifera and a species of Lycopodium). This family is distributed throughout Malaysia but the diversity is not as high as in the Americas, the center of distribution. Morphological studies including branching patterns, anatomy and ultrastructure were conducted as they are taxonomically significant for delimiting genera and species of Lycopodiaceae. The presence of a hair at the tip of the leaf, midvein and subpetiole are good taxonomic leaf characters in some species of Lycopodiaceae. Two basic branching patterns are observed in this study with each corresponding to a distinct genus. The genus Huperzia is characterized by an isotomous branching pattern while Lycopodium and Lycopodiella have anisotomous branching patterns. Additional leaf differentiation characters on the stem of Lycopodiaceae such as heterophylly, homophylly, isophylly and anisophylly were the basis for the classification of genera and some species. The stem anatomy reveals that Lycopodiaceae has a primitive type of stele called protostele in three forms. Palynological studies reveal that spore type, shape, size, surface sculpture and aperture are taxonomically significant for delimiting or distinguishing species. Sporophyll characteristics such as margin, size, shape of leaves and apex are important for identification. Variation in the sporangial wall structure of Lycopodiaceae was found to be taxonomically significant at the genus and species levels. Based on all the characters mentioned here, the Lycopodiaceae are divided into three genera in Malaysia: Huperzia, Lycopodium and Lycopodiella. The current threat to Lycopodiaceae is conversion of hill forest into agriculture land, the main habitat of this family and over-collection by local people as a source of income. Conservation and legislation are needed to safeguard these untapped resources of possible future pharmaceuticals and other yet unknown benefits to mankind.